PENGARUH HARGA TERHADAP KEPUTUSAN PEMBELIAN SEPATU WANITA MERK KICKERS PADA PT MAHKOTA PETRIEDO INDOPERKASA CABANG MATAHARI DEPARTEMEN STORE MALL SKA PEKANBARU - Febrina, Dian (Sekolah Tinggi Ilmu Ekonomi Riau, 2021)
This study aims to determine the effect of price on purchasing decisions for Kickers Women's Shoes at PT Mahkota Petriedo Indoperkasa, Matahari Branch, Department Store, SKA Mall, Pekanbaru. In this study data were collected through a questionnaire to 87 who became respondents. Then performed an analysis of the data obtained in the form of quantitative analysis. The results of data processing t count 8,643> t table 1,988, which means that the price has a significant effect on the purchase decision for Kickers Women's Shoes at PT Mahkota Petriedo Indoperkasa, Matahari Branch, Department Store, Mall SKA Pekanbaru. The effect of price on purchasing decisions for Kickers Women's Shoes at PT Mahkota Petriedo Indoperkasa, Matahari Branch, Department Store Mall, SKA Pekanbaru, is positive as evidenced by the regression coefficient (b) of 0.633. The magnitude of the effect of the price on the purchase decision for Kickers Women's Shoes at PT Mahkota Petriedo Indoperkasa, Matahari Branch, Department Store, SKA Mall, Pekanbaru, is 46.80%.